2022
DOI: 10.1088/1742-6596/2265/2/022009
|View full text |Cite
|
Sign up to set email alerts
|

Farm blockage model validation using pre and post construction LiDAR measurements

Abstract: This study discusses the characterization of farm blockage for an Onshore site. A test campaign was designed to measure the effects of farm induction upstream of a row of turbines. 5 LiDARs were dispersed on a site in North America. Measurement periods took place before and after erection of the turbines. A thorough characterization of the wind conditions is performed using the measurement from the pre-construction period. During nighttime, vertical profiles reveal the occurrence of low-level jet (LLJ) structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…The previous section clearly established that RANS simulations and wind-tunnel measurements predict wind-farm blockage consistently (in-line with comparisons between RANS and full-scale measurements [11,15,22]); yet, it also demonstrated that wind-tunnel confinement reduces blockage, whilst also complicating its prediction. However, for industrial applications, the accurate prediction of blockage in an unconfined setting counts.…”
Section: Effect Of Ti On Farm Blockagesupporting
confidence: 67%
See 1 more Smart Citation
“…The previous section clearly established that RANS simulations and wind-tunnel measurements predict wind-farm blockage consistently (in-line with comparisons between RANS and full-scale measurements [11,15,22]); yet, it also demonstrated that wind-tunnel confinement reduces blockage, whilst also complicating its prediction. However, for industrial applications, the accurate prediction of blockage in an unconfined setting counts.…”
Section: Effect Of Ti On Farm Blockagesupporting
confidence: 67%
“…Whereas a 1% error is certainly acceptable in wake-loss prediction (usually on the order of 10%-35%), it is definitely not in blockage, as the error would be of similar order. In general terms, RANS methods are able to characterise blockage accurately [11,15,28,29], as farm blockage is coupled to the upwind pressure gradient given by the mean flow [24]. Large-Eddy Simulations (LES) capture unsteadiness, a wide range of turbulence scales and energy fluxes, thereby providing a more detailed description of the instantaneous flow field than RANS and catching the interaction between atmosphere and wind farm, especially in buoyancy-driven flows [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…For a low C T , there was little to no impact on the velocity upstream of the wind farm, while for larger C T , the velocity was reduced by 4.5%. Jaquet et al 10 performed a study where the wind speed was measured pre‐ and post‐installation of the wind farm. The results show that the upstream wind speed decreased by up to 3% after the wind farm had been installed.…”
Section: Introductionmentioning
confidence: 99%
“…Several scanning technologies and strategies have been adopted to probe the atmospheric boundary layer for wind energy applications. Profiling lidars have been deployed for freestream resource assessment (Gottschall et al, 2012;Optis et al, 2021;Sharma et al, 2021), wake characterization (Heisel et al, 2018) and plant induction quantification (Jacquet et al, 2022;Letizia et al, 2022). Scanning lidars, i.e., those that feature the ability to direct the laser beam in arbitrary directions (among other abilties), offer additional flexibility and permit a more targeted characterization of the wind plant flow.…”
Section: Introductionmentioning
confidence: 99%